1997
DOI: 10.1207/s15327655jchn1401_3
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Wireless, Pen-Based Computing Among Visiting Nurses in the Inner City: A Qualitative Study

Abstract: The purpose of this qualitative study is to understand how a sample of visiting nurses experienced the practice of home health nursing in the inner city and how they perceived the anticipated introduction of wireless, pen-based computing into their practice. Focus groups were held with visiting nurses 1 week before the introduction of the wireless, pen-based computers. The data were analyzed using Strauss and Corbin's (1990) method for concept development. The following central concepts emerged from the focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Considering that ‘Automated information systems have been part of the health care environment for nearly 30 years (Manning & McConnell, 1997, p. 141), it is surprising that few studies have explored clinicians’ perspectives of using CPIS (Timpka & Johansson, 1994; Karlsson et al. , 1997; Valenta & Wigger, 1997; Wilson & Fulmer, 1997). There are numerous studies of ‘nurses attitudes to’ various aspects of CPIS (see e.g.…”
Section: Background To the Studymentioning
confidence: 99%
“…Considering that ‘Automated information systems have been part of the health care environment for nearly 30 years (Manning & McConnell, 1997, p. 141), it is surprising that few studies have explored clinicians’ perspectives of using CPIS (Timpka & Johansson, 1994; Karlsson et al. , 1997; Valenta & Wigger, 1997; Wilson & Fulmer, 1997). There are numerous studies of ‘nurses attitudes to’ various aspects of CPIS (see e.g.…”
Section: Background To the Studymentioning
confidence: 99%
“…In addition, nurse participants wrote negative comments about device features (data entry, response time, system downtime, and concerns about theft and loss), similar to comments from previous reports. 10,11,19,20 However, the clustering of these negative items in one construct may pose a response bias for the ESPDA, which could be eliminated by changing the language or wording of some items. [34][35][36] Because user concerns about PDA features such as screen size, device theft, and data transmission are not unique to this study, these issues deserve further research and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Early qualitative studies found that although home health nurses welcomed using penbased wireless computers in their daily practice, they were concerned about issues of hardware maintenance, technical support, and device theft or loss. 19,20 Penbased computers improved the quality of documentation for home health nurses compared with manual records by providing immediate access to an easily readable record and decreasing calculation errors, but the time spent on patient care and documentation did not change significantly. 21 In addition, PDAs were used to establish a database for an intravenous resource nurse service, but its use was limited by slow response time after entering large amounts of data and by the attention needed to maintain the hardware (eg, keeping the battery charged, avoiding accidentally dropping the PDA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was also noted in Wilson's US study of visiting nurses. 31 In that study they believed that a totally structured templated note was incomplete. Richards likewise indicated that a template telephone message lacked the personalisation and detail required to prevent future misunderstandings.…”
Section: Physician Concerns: the Graphical User Interface (Gui)mentioning
confidence: 99%